Model Digital Signature Pada Dokumen Formal Akademik - Henderi Henderi; Devi Rositawati; Pipin Romansyah (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
Digital signature system is implemented to improve the quality of document border services. A digital signature on a document means that the signatory knows and approves the document. On the other hand, previous research states that the digital signature model has weaknesses in terms of identifying and verifying the authenticity of the signature image. This study aims to develop a digital signature model with validation of the authenticity of good signatures and accelerate document binder services. The digital signature model was developed using modified agile methods. Model development is done through design, construction, testing, evaluation, and delivery. The test results show that the digital signature model developed in this study is proven to accelerate document publishing services with good validation and simplify the document publishing business process.